Optimization of Drying Temperature and Thickness of Slice in Curcuma Drying Process (Curcuma xanthorrhiza Roxb) with Response Surface Methodology (RSM) - Suryanantha, I Wayan; Yulianti, Ni Luh; Sulastri, Ni Nyoman (Jurnal BETA (Biosistem dan Teknik Pertanian), 2022)
Two main things that influence the drying process of Curcuma; are drying temperature and thickness of slices. This research was conducted to obtain the optimum combination of drying temperature and slice thickness and determine the mathematical model to predict water activity, moisture content, ash content, and Q value through Response Surface Methodology (RSM). The data were processed using the Design Expert ® 12 software. Based on the testing and analysis, the results generated linear and quadratic models on the observed responses. The linear model was generated on water and ash content, while the quadratic model was generated on water activity and Q values. The drying temperature was 65.867 ̊C, and the slice thickness of 3 mm was the chosen optimumcombination. The verification test results show that the actual value of water activity is 0.218 aw, water content is 9.974%, ash content is 3.316%, and Q value is 31.950 kJ/h. The desirability value of the combination of drying temperature and optimum slice thickness of 0.898indicates that 89.8% of the expected response criteria can be achieved.